The Practicality of Developing a Multi-Split Model Based on the Hands-on-Mind Approach as a Reconstruction of Basic Literacy and Character Values - Thamrin, Lily; Ghasya, Dyoty Aulia Gilda; Pranata, Rio (Jurnal Ilmiah Peuradeun, 2023)
West Kalimantan is a province in Indonesia with the longest border with foreign countries. Therefore, education in these areas must be paid close attention to so that students can obtain optimal learning competency results and master basic literacy and character values as catalysts for understanding, awareness, and attitudes toward the pillars of national and state life. This study aims to determine the practicality of developing a multi-split model based on the hands-on-mind approach that can be used to reconstruct basic literacy and character values in the border areas of West Kalimantan and Malaysia during the COVID-19 pandemic. The research method used was research and development (R&D). The source of the data in this study was obtained from the results of field trials; thus, the practicality of developing a multi-split model based on the hands-on-mind approach observed by two teachers could be seen. The results of the practicality analysis showed that (1) the implementation of learning using a multi-split model based on a hands-on-mind approach reached an average score of 3.23 with good criteria, (2) student activities got an average score for each activity of at least 3.16 with good criteria and (3) the obstacles experienced by students were not familiar with the pattern of the learning process using this model; consequently several student activities could not run optimally.